The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1179/106698109791352201
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of the Lumbar Plexus: A Descriptive Anatomy Study with Proposed Clinical Implications

Abstract: Evidence-based practice emphasizes the examination and application of evidence from clinical research into diagnosis, prognosis, and outcomes based on a formal set of rules 1 . One method of evaluating evidence is to assign levels of evidence 2 . In this evidence hierarchy, extrapolations from basic science research are classified as the lowest level of evidence. However, especially in situations where higher-level research evidence is insufficient, such extrapolation based on a thorough knowledge of relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
82
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 15 publications
4
82
0
5
Order By: Relevance
“…Depending on the specific innervation of the AON, patients may present with diverse symptomology. Due to its innervation of the hip joint, a differential diagnosis for groin pain could be compression of the AON [6]. If there is variation in the of the AON, as in the presently reported case, it could lead to weakness in flexion of the hip due to the innervation of the psoas major by the AON.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Depending on the specific innervation of the AON, patients may present with diverse symptomology. Due to its innervation of the hip joint, a differential diagnosis for groin pain could be compression of the AON [6]. If there is variation in the of the AON, as in the presently reported case, it could lead to weakness in flexion of the hip due to the innervation of the psoas major by the AON.…”
Section: Discussionmentioning
confidence: 72%
“…The branches of the lumbar plexus and its association with the psoas major muscle is important to understand, especially during surgery in that region or when performing anesthetic blocks. Variations of the plexus and their associated clinical implications have been documented in the literature [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LPB provides mostly favorable postoperative analgesia but can produce incomplete analgesia. Incomplete analgesia may perhaps be due to the various components of the lumbar plexus being physically separated by muscle tissue such that the infused local anesthetic solution cannot reach them all [1,2,10]. The case reports of Lee et al [12] demonstrated that L1-L2 PVBs provided adequate pain relief in patients undergoing hip arthroscopy; however, the study of Bogoch et al [6] demonstrated that opioid consumption was significantly less during the first 4 hours after performing paravertebral blocks compared to a sham procedure in patients undergoing THA, but no significant difference was seen in opioid consumption thereafter.…”
Section: Discussionmentioning
confidence: 99%